Sosialisasi Efektifitas Penggunaan Sosial Media untuk memulai Start Up bisnis di Usia Remaja - Laily Nur Aini; Siti Maisaroh; Nurul Qomariyah (Institut Nalanda, 2024)
The importance of social media as a start-up marketing strategy in Indonesia is something that must be considered, especially for teenagers in the current industrial era 4.0. Social media has a big influence on marketing activities in the era of digitalization, where by using social media, the business we market can become famous and become a start-up company. The aim to be achieved in this service is to increase insight and provide motivation for students of SMK N 2 Sampang about the effectiveness of using social media to start a business start-up and make it easier for students to carry out low-fund based businesses that are effective and efficient in accordance with the needs of teenagers. even adults who want to start a business. The method used in this community service uses survey, lecture and discussion methods. It is hoped that this socialization will be able to provide motivation to teenage students to use social media to start a business start-up. This community service provides benefits for both partners or participants (students), namely; (1) increasing knowledge of the use of social media, success factors for Start Ups, utilizing social media to start and maintain a business; and (2) after attending the training, participants expressed a high level of satisfaction with the implementation.